Adsorción de Cromo (III) mediante nanopartículas de hierro recubiertas con Titania en aguas simuladas del sector curtiembre (2022)
In Colombia in 2015, 406,078 tons of hazardous waste were produced, of which about 28% were discarded untreated. In this sense, the tannery sector uses chromium salts to stabilize the collagen fibers, adding chromium to the process effluent. Chromium is a heavy metal, which due to its bioaccumulation and persistence in water generates environmental and health problems. For this reason, a nanocomposite with reduced toxicity and low cost, with an iron oxide core coated with titanium oxide was developed to remove chromium from effluents.